ISLAM AND NEO-MODERNISM IN INDONESIA: REVISITING NURCHOLISH MADJID AND ABDURRAHMAN WAHID’S THOUGHT ON CIVIL SOCIETY - Dito Alif Pratama (Al'Adalah, 2023)
Nurcholish Madjid and Abdurrahman Wahid are regarded as two of Indonesia's most influential Muslim intellectuals at the turn of the twentieth century. Adapting the concept of Barton (1997), both Madjid and Wahid are not only prominent public intellectuals but also can be considered intellectual ulama, scholars who combine the best of classical scholarship and intellectual leadership with modern secular and Islamic learning and participated alongside other public intellectuals in Indonesia's civil society forums. In addition, Greg Barton labels these personalities and characteristics of thought as Neo-Modernists or Neo-Modernist thinkers. This paper examines the interpretation of Madjid, who studied in a more Western academic culture, and Wahid, who studied in a Middle-Eastern country, on civil society as the manifestation of both Neo-Modernism's thought, followed by a discussion on the similarities and differences between the two ideas. Through an exploratory and comparative analysis, this study reveals that the Neo-Modernism interpretation of civil society articulated by both can be seen in their progressive thought towards Islam and society, Madjid with his idea of 'secularization' and further changed into 'de-sacralization'; while Wahid with his thinking on the indigenization of Islam (pribumisasi Islam). Their thoughts introduce an open, inclusive, progressive understanding of the relationship between Islam and civil society, asserting social pluralism and modernity and stressing the need for tolerance and understanding. Moreover, this paper also argues that both interpretations of Islam and civil society have been constructive for Indonesia in promoting democratic reforms, strengthening the importance of the Pancasila (the five pillars) foundation and state constitution, not religious sectarianism (theocracy), thus refuting the notion that Islam is incompatible with democracy and pluralism and assisting Indonesian society in the productive synthesis of Islamic ideas and modern concepts such as democracy, liberalism, and secularism.